Day 3 Wed, November 11, 2015 2015
DOI: 10.2118/177505-ms
|View full text |Cite
|
Sign up to set email alerts
|

Gas Injection EOR Screening by Laboratory Experiment and Sector Modeling in Carbonate Reservoir

Abstract: Hydrocarbon gas injection projects are undertaken in order to maintain reservoir pressure, produce oil through swelling and reduce residual oil saturation by decreasing the interfacial tension (IFT). Along with local displacement efficiency, macroscopic sweep efficiency plays a dominant role in the success of gas injection projects, as recovery from the field depends strongly on reservoir geology and petrophysical properties.In this paper, a procedure to screen the best injectant for implementation of a succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…PVT experiments showed that the minimum miscibility pressure (MMP) is around 4500 psia, which is higher than initial reservoir pressure; but the crude oil has a strong swelling effect (swells by a factor of 1.45 once saturated with gas). Unsteady-state coreflood experiments performed with a 200 cm long core showed recovery of 70% for immiscible flood while recovery of 92% for miscible flood (Kumar et al, 2015).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…PVT experiments showed that the minimum miscibility pressure (MMP) is around 4500 psia, which is higher than initial reservoir pressure; but the crude oil has a strong swelling effect (swells by a factor of 1.45 once saturated with gas). Unsteady-state coreflood experiments performed with a 200 cm long core showed recovery of 70% for immiscible flood while recovery of 92% for miscible flood (Kumar et al, 2015).…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, local grid refinement allowed more accurate representation of well trajectories, which was difficult in large gridcells of full field model. A value of 5% residual oil to miscible flood (S orm ), obtained from coreflood experiments (Kumar et al, 2015), was used to restrict the vaporization of oil components into gas phase below the user defined residual oil saturation in a grid block (Hiraiwa et al, 2007;Bourgeois et al, 2011).…”
Section: Model Descriptionmentioning
confidence: 99%
“…Laboratory experiments should be carried out to determine the feasibility of hydrocarbon injection before field implementation. Kumar et al (Kumar et al 2015) conducted pressure/volume/temperature (PVT) experiments and core displacement experiments of natural gas in combination with hydrocarbon gas injection projects of carbonate reservoirs. The results show that the minimum miscible pressure (MMP) of injected natural gas is somewhat higher than the initial reservoir pressure, but crude oil has a strong swelling effect (once saturated by gas, the swelling rate can reach 1.45 times).…”
Section: Hydrocarbon Gas Floodingmentioning
confidence: 99%
“…Down-flank gas injection pilot Gas injection pilots (GIP) were implemented in the north-west area of the field to assess the secondary and tertiary gas sweep efficiency in down-flank area for long term development plan. The injected gas was the 1 st stage separator gas of which minimum miscibility pressure is higher than the field initial pressure (Kumar et al, 2015a). The pilot results are summarized as (a) gas movement in the pilot area was dominated by pressure gradient of the peripheral water injection, (b) significant gas override was observed, (c) high recovery occurred when injected gas achieved miscibility and (d) asphaltene precipitation was observed in one of the pilots (Kumar et al, 2015b).…”
Section: Peripheral Water Injectionmentioning
confidence: 99%